2012
DOI: 10.1038/ijo.2011.257
|View full text |Cite
|
Sign up to set email alerts
|

Six-minute walking test predicts maximal fat oxidation in obese children

Abstract: BACKGROUND: Obesity is associated with reduced exercise maximal fat oxidation rate (FATmax), which is generally assessed by cardiopulmonary cycling test. The six-minute walking test (6MWT) presents an alternative method in patients. OBJECTIVE: The aim of this study was to establish a practical reference equation facilitating the prediction of FATmax from the 6MWT in obese children of both genders. DESIGN: This study is a cross-sectional study using mixed linear and multiple regression models. RESEARCH METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
1
21
0
3
Order By: Relevance
“…The quality of the studies on children with Duchenne muscular dystrophy [31], and obesity [33] was rated fair and good respectively. Main methodological flaws included inadequate statistical procedures, (24)inappropriate time intervals between tests (27)(28)(29) and ambiguity about independent administrations. (24,27)Six studies reached high levels of test-retest reliability (ICC_.84 -.98), and 1 study showed a strong correlation between the test and retest, (rp_.90, P_.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the studies on children with Duchenne muscular dystrophy [31], and obesity [33] was rated fair and good respectively. Main methodological flaws included inadequate statistical procedures, (24)inappropriate time intervals between tests (27)(28)(29) and ambiguity about independent administrations. (24,27)Six studies reached high levels of test-retest reliability (ICC_.84 -.98), and 1 study showed a strong correlation between the test and retest, (rp_.90, P_.001).…”
Section: Resultsmentioning
confidence: 99%
“…Hypothesis testing (validity): Hypothesis testing was performed in studies, convergent validity was assessed in studies, and discriminative validity was assessed in studies. The methodological quality of the studies regarding children with obesity was rated fair [14,28] and poor [33]. The quality of the studies on children with cystic fibrosis was rated fair [25] and poor [24].…”
Section: Resultsmentioning
confidence: 99%
“…In most of the studies involving field analysis, for evaluation of physical fitness, 6MWT is preferred over other laboratory tests. In our study we had used 6MWD to study their physical fitness because it has following benefits such as walking is one of the normal activities of life reflecting the capacity to do daily activities (Makniet al, 2012), it is simple, easy to administer, it has low cost and can be used in routine (Makni et al, 2012;Kanburoglu, 2014;Roush, 2006;Geiger et al, 2010;Ulrich et al, 2013) validated to have high correlation with workloads, HR, oxygen saturation & dyspnoea responses when compared with standard cycle ergometry& treadmill exercise tests (Makniet al, 2012;Kanburoglu, 2014;Roush, 2006;Ulrich et al, 2013), direct correlation with quality of life which enables an individual to cope against disease process and remain independent (Makniet al, 2012;Ulrich et al, 2013), provides opportunity to evaluate patient in a timely, practical and economical manner (Makniet al, 2012;Ulrich et al, 2013), repeated measurements are possible as the patient has to be evaluated in a disease progression manner (Makniet al, 2012;Geiger et al, 2010;Ulrich et al, 2013) relationships found between 6MWD and crude power and / or HR at which fat oxidation reaches its maximum is the most useful information in targeting the planning of training procedure (Makni et al, 2012;Geiger et al, 2010. However, there are various drawbacks of 6MWD as it may not change with increase in age because of ever-changing hormones and energy levels or discrepancy of inner motivation of children at different ages.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure [56,57] COPD [58−60] Primary pulmonary hypertension [61−63] Peripheral arterial disease [64−66] Chronic liver diseases [67], qualification for liver transplantation [68] Lung injury in other conditions: Radiation-induced pulmonary toxicity [69] Evaluation of functional capacity in children [70,71] Pulmonary hypertension [72] Evaluation of selected metabolic parameters [73] Diabetes mellitus [74] Cerebral palsy [75], neuromuscular diseases [76][77][78][79] Qualification for lung transplantation in cystic fibrosis [80] Literature data indicate that 6MWT is a safe procedure. Despite the large number of tests performed, there are no reports on serious complications, even in patients with heart failure and other diseases [6, 91−93].…”
Section: Predicting Survivalmentioning
confidence: 99%